Textile Industry of Uzbekistan: Achievements and Problems (Texas Journal of Engineering and Technology, 2022)
The introduction of continuous forms of organization of production was identified as a priority for textile enterprises as the most important condition and source of measures for the development of the country's textile industry and the production of export-oriented products. In this regard, the article examines some of the problems of the formation of a modern competitive national textile industry in the Republic of Uzbekistan. And on this basis, priorities were developed for the development of the textile industry for the medium term.